Multimorbidity and mortality in Ontario, Canada: A population-based retrospective cohort study. (26th August 2020) - Ryan, BL; Allen, B; Zwarenstein, M; Stewart, M; Glazier, RH; Fortin, M; Wetmore, SJ; Shariff, SZ
Objective: To examine the relationship between multimorbidity and mortality, and whether relationship varied by material deprivation/rural location and by age. Methods: Retrospective population-based cohort study conducted using 2013–14 data from previously created cohort of Ontario, Canada residents classified according to whether or not they had multimorbidity, defined as having 3+ of 17 chronic conditions. Adjusted rate ratios were calculated to compare mortality rates for those with and without multimorbidity, comparing rates by material deprivation/rural location, and by age group. Results: There were 13, 581, 191 people in the cohort ages 0 to 105 years; 15.2% had multimorbidity. Median length of observation was 365 days. Adjusted mortality rate ratios did not vary by material deprivation/rural location; overall adjusted mortality rate ratio was 2.41 (95% CI 2.37–2.45). Adjusted mortality rate ratios varied by age with ratios decreasing as age increased. Overall rate ratio was 14.7 (95% CI 14.48–14.91). Children (0–17 years) had highest ratio, 40.06 (95% CI 26.21–61.22). Youngest adult age group (18–24 years) had rate ratio of 9.96 (95% CI 7.18–13.84); oldest age group (80+ years) had rate ratio of 1.97 (95% CI 1.94–2.04). Conclusion: Compared to people without multimorbidity, multimorbidity conferred higher risk of death in this study at all age groups. Risk was greater in early and middle adulthood than in older ages. Results reinforce the fact multimorbidity is not just a problem of aging, and multimorbidity leads not only to poorer health and higher health care utilization, but also to a higher risk of death at a younger age.